Pendekatan Maqashid Syariah Indeks (Msi) Terhadap Kinerja Bank Syariah Mandiri Di Indonesia - Nurhalimah Lubis; Rizki Pratiwi Harahap; Syarifah Isnaini (CERED Indonesia Institute, 2023)
theory put forward by Mustafa Omar Mohammed which explains the concept of maqashid shari'ah by dividing it into three main objectives, namely: tahzib al-fard (educating individuals), iqamah al-adl (enforcing justice), and jalb al-maslahah (maintaining benefit). This type of research is a qualitative research with a descriptive approach. The data used in this study is secondary data from the 2018 - 2020 annual report obtained from the official website of Bank Syariah Mandiri during the research period. The data collection used is a documentation technique in the annual report financial reports published by the OJK. The data is obtained and processed by reviewing report data, calculating and interpreting it. Based on the calculation results, it is known that in 2019 financial performance based on the sharia maqashid index achieved the highest achievement at Bank Syariah Mandiri with a sharia maqashid index of 2.27 and in 2018 and 2020 the lowest achievement was at Bank Syariah Mandiri with a sharia maqashid index of 0. 09.